Interactions of Organic Solvents at Graphene/α-Al2O3 and Graphene Oxide/α-Al2O3 Interfaces Studied by Sum Frequency Generation - Achtyl, Jennifer L; Vlassiouk, Ivan V; Dai, Sheng; Geiger, Franz (Journal of physical chemistry. C, 2014)
The adsorption of 1-hexanol from cyclohexane-d 12 at single-layer graphene/α-Al2O3 interfaces was probed at mole percent values as low as 0.05 in the C–H stretching region using vibrational sum frequency generation (SFG). The SFG spectra are indiscernible from those obtained in the absence of graphene, and from those obtained in the presence of graphene oxide films prepared via oxygen plasma treatment of pristine single-layer graphene. A Langmuir adsorption model yields observed free adsorption energies of −19.9(5) to −20.9(3) kJ/mol for the three interfaces. The results indicate that the molecular structure of the hexanol alkyl chain is subject to the same orientation distribution when graphene, oxidized or not, is present or absent at the α-Al2O3/cyclohexane-d 12 interface. Moreover, it appears that the adsorption of 1-hexanol in this binary mixture is driven by hexanol interactions with the underlying oxide support, and that a single layer of graphene does not influence the extent of this interaction, even when defects are introduced to it. Finally, our structural and quantitative thermodynamic data provide important benchmarks for theoretical calculations and atomistic simulations of liquid/graphene interfaces. We hypothesize that defects emerging in graphene during operation of any device application that relies on layered solvent/graphene/oxide interfaces have little impact on the interfacial structure or thermodynamics, at least for the binary mixture and over the range of defect densities probed in our studies.